The Role of Self-Control in Reducing FOMO-Driven Impulsive Buying among Students - Achmad Basofitrah; Mohammad Zainullah; Muhammad Irsyad Baitussalam (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The rapid growth of social media and e-commerce has intensified impulsive buying behavior among university students, particularly through psychological pressures associated with Fear of Missing Out (FOMO) and continuous digital exposure. Although previous studies have examined the direct effects of FOMO, social media intensity, and self-control on consumer behavior, limited attention has been given to the buffering role of self-control in weakening these influences within higher education settings. This study investigates the effects of FOMO and social media intensity on impulsive buying behavior and examines the moderating role of self-control among students of Institut Badri Mashduqi (IBAMA). Using an explanatory quantitative approach, data were collected from 180 students through purposive sampling and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results reveal that FOMO and social media intensity positively and significantly influence impulsive buying behavior, whereas self-control has a significant negative effect. Furthermore, self-control significantly moderates the relationships between FOMO, social media intensity, and impulsive buying by reducing the strength of these effects. This study contributes to the digital consumer behavior literature by demonstrating the protective role of self-control as a psychological buffering mechanism and provides practical implications for developing digital literacy and self-regulation programs among university students.